The Papers of Jefferson Davis : June 1865-December 1870 - Davis, Jefferson, 1808-1889 (Book collections on Project MUSE., 2008)
""Being powerless to direct the current, I can only wait to see whither it runs, "" wrote Jefferson Davis to his wife, Varina, on October 11, 1865, five months after the victorious United States Army took him prisoner. Indeed, in the tumultuous years immediately after the Civil War, Davis found himself more acted upon than active, a dramatic change from his previous twenty years of public service to the United States as a major political figure and then to the Confederacy as its president and commander in chief. Volume 12 of The Papers of Jefferson Davis follows the former president of the Conf.